Effects of diet manipulation on growth performance, carcass characteristics, and meat quality of intact male pigs - Maloney, C.A.; Hines, Robert H.; Cao, H.; Park, J.S.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Castrates were predictably less efficient, had greater ADFI, and tended to have more BF than contemporary boars. Castration decreased detection of boar taint, but alterations of dietary CP, pH, and antimicrobial level from 225 to 276 lb had no effect on sensory panel perception of odor from fat of intact males.
Keywords: Swine; Boars; Diet; Boar odor